Endoscopically Assisted Crawford Tube Placement Results in Shorter General Anesthesia Times in Pediatric Patients. Issue 1 (January 2018) - Dobberpuhl, Mitchell R.; Timoney, Peter J.; Comer, Brett T.
Background: Crawford tube placement is commonly used to achieve patency of nasolacrimal ducts for epiphora secondary to nasolacrimal duct obstruction. The nasal passages of pediatric patients are narrower than adults, and the result is a relatively higher risk of intranasal complications (e.g., synechiae, bleeding) with Crawford tube placement. There is evidence that general anesthesia may negatively affect the neurocognitive function and behavioral development of children, which prompts efforts to decrease operation times for potential health benefits and also potentially to reduce health care costs. Analysis ofresearch reports supports the use of nasal endoscopy to reduce intranasal complications with Crawford tube placement; however, no publications currently address the effect of nasal endoscopy concurrent with Crawford tube placement on operative times on pediatric patients or the resulting effects on health care costs. Objective: To determine the difference in procedure time and cost between Crawford tubes placed traditionally and those placed with endoscopic assistance in pediatric patients. Methods: A chart review was performed from January 1, 2011 to December 31, 2016 for cases using CPT codes 68815 or 31231. Within this group of patients, the patient in whom nasal endoscopy was performed were placed in the "endoscopic" group and the patients without endoscopy were placed in the "traditional" group. Procedure times were noted, and the t-test was performed to examine for any statistically significant difference in operative times. Estimates of anesthesia cost savings were made. We identified 24 patients in the traditional group and 7 patients in the endoscopic group. Results: The average operative time for the traditional group was 27.3 minutes compared with 14.0 minutes for the endoscopic group (p = 0.02). The cost comparison data revealed no significant difference with the traditional group averaging $9369 per procedure and the endoscopic group averaging $8891 (p = 0.51). Conclusion: An endoscopically assisted Crawford tube placement resulted in patients who had less time under general anesthesia compared with the traditional technique at no difference in cost.